Program for Biosafety Systems (PBS) - International Food Policy Research Institute (2011)
The Program for Biosafety System (PBS) supports partner countries in Africa and Asia in the responsible development and use of biotechnology. Managed by the International Food Policy Research Institute (IFPRI), PBS works with countries interested in using biotechnology to enhance agricultural innovation.